2004
DOI: 10.1674/0003-0031(2004)152[0063:ioipia]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraspecific Polyploidy in Andropogon gerardii (Poaceae) Populations

Abstract: ABSTRACT.-Andropogon gerardii populations are comprised of two (or more) polyploid forms over much of the range of the species. To understand the impact of intraspecific polyploidy, polyploid cytotypes were compared over 4 y in native grasslands in Boulder, Colorado. Boulder A. gerardii populations averaged 59.6% hexaploids (60 chromosomes), 35.3% enneaploids (90 chromosomes) and 5.1% intermediate (aneuploid) chromosome numbers using flow cytometry to infer chromosome numbers. Neither mean clone area nor mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…Recently, with the development of flow cytometry as a tool for assessing DNA content and ploidy in plants, large-scale assessment of cytotype distribution patterns has became possible (Kron et al 2007) revealing surprisingly widespread co-occurrence of several cytotypes (Keeler 2004;Halverson et al 2008;Stahlberg 2009) despite theoretical assumptions that without reproductive isolation, local cytotype co-occurrence is unstable and frequency-dependent selection will exclude the cytotype in minority (Levin 1975;Felber 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the development of flow cytometry as a tool for assessing DNA content and ploidy in plants, large-scale assessment of cytotype distribution patterns has became possible (Kron et al 2007) revealing surprisingly widespread co-occurrence of several cytotypes (Keeler 2004;Halverson et al 2008;Stahlberg 2009) despite theoretical assumptions that without reproductive isolation, local cytotype co-occurrence is unstable and frequency-dependent selection will exclude the cytotype in minority (Levin 1975;Felber 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The association between clonal reproduction and polyploidy was first reported in the late 1940s [29]. Recent studies aimed at the effect of ploidy variation on genotypic diversity in clonal species [32, 33], and more specifically on clonal size [34], however, indicate that polyploids are not more clonal compared to conspecific diploids and that it is hardly possible to draw any general conclusions about the interactions between clonality and polyploidy. On the other hand, it has been shown that lateral spread is a prerequisite for polyplodization, as it can compensate for the lower efficiency of generative reproduction in some polyploids.…”
Section: Introductionmentioning
confidence: 99%
“…However, meiosis in the enneaploids is irregular leading to defective gametes. Keeler (2004) also found that hexaploids had a higher frequency of viable seeds than enneaploids. Flow cytometric examination is needed to determine the ploidy levels within populations in the Carolinas.…”
Section: Discussionmentioning
confidence: 90%
“…Polyploidy is reported for populations of big bluestem from midwestern studies (Keeler 1992, Norrmann et al 1997, Keeler 2004. Norrmann and colleagues (1997) reported that 6x (hexaploid) and 9x (enneaploid) big bluestem cytotypes are inter-fertile in midwestern populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation